G‑Quadruplex/Porphyrin Composite Photosensitizer: A Facile Way to Promote Absorption Redshift and Photodynamic Therapy Efficacy - Cheng, Meng; Cui, Yun-Xi; Wang, Jing; Zhang, Jing; Zhu, Li-Na; Kong, De-Ming (ACS applied materials & interfaces, 2019)
Photosensitizer is one of the most important elements of photodynamic therapy (PDT). Herein, we reported a novel strategy to prepare a new series of composite photosensitizers. The composite photosensitizer was prepared by simply mixing DNA G-quadruplexes with a hydrophilic porphyrin (TMPipEOPP)4+·4I–. Compared with the conventional porphyrin photosensitizers, the excitation wavelength of the composite one has been ∼50 nm redshifted (from 650 to 700 nm), which is beneficial to the penetration of the light. Moreover, the composite photosensitizer showed an about 7.4-fold increase of light absorption efficiency, thus greatly enhancing the singlet oxygen (1O2) generation capacity and PDT efficacy. What is more, the introduction of nucleic acids in the composite photosensitizer could also provide some extra charming properties, such as the targeted recognition ability conferred by aptamer and high capability to assemble with various drug carriers. We demonstrated that the composite photosensitizer could be easily assembled with MnO2 nanosheet. The obtained nanodevice integrated the merits of a composite photosensitizer and MnO2 nanosheet, thus showing strong near-infrared absorption, high 1O2 generation efficiency, avoidance of nonideal 1O2 consumption by glutathione, and in situ O2 generation to relieve tumor hypoxia. This nanodevice showed greatly improved PDT efficacy both in vitro and in vivo, presenting a huge potential for applications in clinical therapy for tumors.